2018
DOI: 10.7897/2230-8407.0812259
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on Antioxidant and Anti-Inflammatory Activities of Ethanolic Extracts of True Mangrove and Mangrove Associate Located in Bhatye Beach Areas of Maharashtra, India

Abstract: The present study showed that among the phytochemicals both the mangroves revealed presence of flavonoids, tannins, triterpenes, alkaloids and saponins. Antioxidant and Anti-inflammatory activity of leaves, stems, pods and fruits of ethanolic extract of Derris trifoliata and Sonneratia alba mangrove species were studied. Total flavonoid content (TFC) was found to be maximum in S.alba fruits of ethanolic extract (792.6 mg quercetin equivalent QE/g) as well as the total phenolic content (TPC) was found to be hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Kumari et al70 dealt with meth-anolic leaf extract of R. mucronata of southeast coast of India, which notably demonstrated anti-inflammatory action at the concentration of 400 mg equivalent to the conventional medicine diclofenac sodium. There was a comparable investigation done by Ray et al [71], who gathered mangrove samples of Sundarban mangrove environment and observed that R. mucronata leaves displayed an in-vitro anti-inflammatory activity in RAW264.7 cell line by MTT test. The impact of the ethanolic extract of R. mucronata leaves (25,50,100,200 and 400µg/ml) on the viability of unstimulated RAW264.7 cells was examined using the MTT assay.…”
Section: Crista Fever Nutsupporting
confidence: 55%
See 1 more Smart Citation
“…Kumari et al70 dealt with meth-anolic leaf extract of R. mucronata of southeast coast of India, which notably demonstrated anti-inflammatory action at the concentration of 400 mg equivalent to the conventional medicine diclofenac sodium. There was a comparable investigation done by Ray et al [71], who gathered mangrove samples of Sundarban mangrove environment and observed that R. mucronata leaves displayed an in-vitro anti-inflammatory activity in RAW264.7 cell line by MTT test. The impact of the ethanolic extract of R. mucronata leaves (25,50,100,200 and 400µg/ml) on the viability of unstimulated RAW264.7 cells was examined using the MTT assay.…”
Section: Crista Fever Nutsupporting
confidence: 55%
“…Mangrove plants have been employed for their therapeutic characteristics by the coastal inhabitants of India for the treatment of inflammation, painful arthritis, antioxidant, diabetes, hepatoprotective activities, asthma, tu-mor, rheumatism, anti-nociceptive and antipyretic activity [63][64][65][66]71]. However, in the Indian environment, on-ly restricted investigations have been undertaken for the separation and purification of bioactive chemicals from mangroves plants.…”
Section: Status Of Biological Study Using Marine Flora In Animentioning
confidence: 99%
“…The medicinal properties of the plant depend upon its phytochemical composition. The mangroves have shown diverse classes of secondary metabolites therefore possess several medicinal properties like antimicrobial 25 , antiviral activities 26 , antioxidant 27 , and anti-inflamatory 28 . The antidiabetic properties of mangrove plants are related to alkaloid, flavonoid, saponin and terpenoids 29 .…”
Section: Discussionmentioning
confidence: 99%